PERLINDUNGAN HUKUM BAGI PEMULIA TANAMAN - TITIN TITAWATI; ALINE FEBRYANI LOILEWEN; GEDE TUSAN ARDIKA (Universitas Mahasaraswati Mataram, 2020)
This study aims to study and to analyze the legal protection for plant breeders and law enforcement for Plant Variety Protection (PVP). This research is a normative legal research, which is based on written legislation and various literatures related to this issue. The form of legal protection for plant breeders is Law Number. 29 of year 2000 concerning Protection of Plant Varieties, has provided legal protection for plant breeders, through Law No. 12 of year 1992 concerning the Plant Cultivation System (UUSBT) and Law No. 29 of year 2000 (UUPVT), UUPVT provides protection for breeders 'economic rights, while UUSBT provides protection for breeders' moral rights. Law enforcement against violations of PVP has been done well, this is evidenced by several cases submitted to the Court, but there are still some cases that are wrong in the application of the law. It is expected that the implementation of the PVP Invitation Act is more optimal